2006
DOI: 10.1007/s00425-005-0182-z
|View full text |Cite|
|
Sign up to set email alerts
|

Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests

Abstract: Mannose binding Allium sativum leaf agglutinin (ASAL) has been shown to be antifeedant and insecticidal against sap-sucking insects. In the present investigation, ASAL coding sequence was expressed under the control of CaMV35S promoter in a chimeric gene cassette containing plant selection marker, hpt and gusA reporter gene of pCAMBIA1301 binary vector in an elite indica rice cv. IR64. Many fertile transgenic plants were generated using scutellar calli as initial explants through Agrobacterium-mediated transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 62 publications
(81 reference statements)
1
77
0
1
Order By: Relevance
“…Concerns about possible consequences to higher animals of ingesting snowdrop lectin have limited further progress, although a recent study incorporating a 90-d feeding trial found no adverse effects resulting from consumption of transgenic rice expressing GNA by rats (Poulsen et al, 2007). Similar partial resistance to hemipterans has also been obtained by expression of a Man-specific lectin from garlic (Allium sativum) leaves (ASA-L) in transgenic rice (Saha et al, 2006a) and a variety of other transgenic plant species. The transgenic rice plants expressing ASA-L were shown to decrease transmission of Rice tungro virus by its insect vector, presumably as a result of decreased feeding by the pest (Saha et al, 2006b).…”
Section: Lectins and Sap-sucking Pestsmentioning
confidence: 99%
“…Concerns about possible consequences to higher animals of ingesting snowdrop lectin have limited further progress, although a recent study incorporating a 90-d feeding trial found no adverse effects resulting from consumption of transgenic rice expressing GNA by rats (Poulsen et al, 2007). Similar partial resistance to hemipterans has also been obtained by expression of a Man-specific lectin from garlic (Allium sativum) leaves (ASA-L) in transgenic rice (Saha et al, 2006a) and a variety of other transgenic plant species. The transgenic rice plants expressing ASA-L were shown to decrease transmission of Rice tungro virus by its insect vector, presumably as a result of decreased feeding by the pest (Saha et al, 2006b).…”
Section: Lectins and Sap-sucking Pestsmentioning
confidence: 99%
“…A few examples of transgenes for pest protection that have already been used in rice transformation and could become available in Vietnam and elsewhere include Bt and cowpea trypsin inhibitor genes for resistance to lepidopteran larvae (High et al, 2004;Huang et al, 2005), lectin genes for resistance to sucking insects (Nagadhara et al, 2003;Saha et al, 2006), chitinase or allene oxide synthase genes for resistance to fungal diseases (Datta et al, 2001;Mei et al, 2006), and trangenes for resistance to bacterial blight (Zai et al, 2004). Other transgenic traits that could be released separately or in combination with various types of pest resistance include resistance to commonly used herbicides, greater tolerance of abiotic stresses, and enhanced production of pro-vitamin A (e.g., Lu and Snow, 2005).…”
Section: 15mentioning
confidence: 99%
“…Some lectins, such as the garlic bulb lectin, play a dual role as storage protein and as defense proteins that are mobilized against attacking insects Smeets et al, 1997;Dinant et al, 2003). Transgenic rice (Oryza sativa) plants expressing garlic leaf agglutinin have antifeedant properties that are insecticidal against sap-sucking insect pests such as the brown planthopper, the green leafhopper (Nephotettix virescens; Saha et al, 2006), and the Egyptian cotton leafworm (Sadeghi et al, 2008).…”
mentioning
confidence: 99%